Reduction of Axial Forces in Column in Multistoried Building using Optimum Size Approach at Earthquake Zone III - Kushwaha, Nitesh; Vishwakarma, Arvind (International Journal of Advanced Engineering Research and Science, 2022)
In India, construction plays a very important role with the introduction of high-rise structures that has been increasing gradually. Along with this, the structure should be strong enough that each element should be economic and strong. The Reduction of Axial forces in Columns in Multistory building using Optimum size change approach is a new idea. It reduces the size of columns at the different levels of the building to reduce its self-weight. On other hand, the structural weight should be minimized when the self-weight of the same will be reduced and proved to be an economic structure. In this project a G+13 Storey structure is analyzed using six different cases named as OS Case A to OS Case F assumed to be situated in seismic Zone III. The plinth area is in use as 625 m2 and all the cases have compared with each parameter. The project concluded that efficient Case is OS Case E on comparing 6 maximum axial force reduction cases that ultimately reduce the overall cost of the project.